2007
DOI: 10.1016/j.mrgentox.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Automated human blood micronucleated reticulocyte measurements for rapid assessment of chromosomal damage

Abstract: This study evaluated the utility of human blood micronucleated reticulocyte (MN CD71+ ) frequency measurement as a cytogenetic damage biomarker. The analytical methodology was flow cytometry in conjunction with a previously described three color fluorescence labeling technique that includes anti-CD71 to focus analyses on the most immature fraction of reticulocytes [Dertinger et al., Environ. Molec. Mutagen., 44:427-435 (2004)]. Blood specimens from fifty self-reported healthy adult volunteers were studied. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 44 publications
0
19
0
7
Order By: Relevance
“…Rodent-based micronucleus tests have become an important component of regulatory safety assessment [23, 24]. More recently, studies involving human blood samples have indicated its effectiveness at detecting chromosomal damage caused by a variety of exposure situations, including a variety of anti-neoplastic chemo- and radiotherapies [25, 26], tobacco use [27], and Zidovudine for the prevention of HIV transmission from infected mothers to their infants [28]. To enumerate micronucleated reticulocytes, whole blood was collected and fixed with −80°C methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Rodent-based micronucleus tests have become an important component of regulatory safety assessment [23, 24]. More recently, studies involving human blood samples have indicated its effectiveness at detecting chromosomal damage caused by a variety of exposure situations, including a variety of anti-neoplastic chemo- and radiotherapies [25, 26], tobacco use [27], and Zidovudine for the prevention of HIV transmission from infected mothers to their infants [28]. To enumerate micronucleated reticulocytes, whole blood was collected and fixed with −80°C methanol.…”
Section: Methodsmentioning
confidence: 99%
“…4 Quantitative HJB HJB were quantitated in a central laboratory by flow cytometric evaluation of at least 10 6 mature (CD71 ؊ ) erythrocytes (Litron Laboratories). 6 Higher proportions of HJB in peripheral blood suggest a decline in spleen function. Values Ͼ 300/10 6 erythrocytes have been associated with loss of splenic filtrative function.…”
Section: Pit Countsmentioning
confidence: 99%
“…Chromosomal aberrations, at present specifically the dicentric assay, remain the gold standard for radiation biodosimetry [69, 70] (Figure 2). New approaches to biodosimetry are in development that also quantify chromosomal damage and include assays that examine for micronuclei in hematopoietic cells [71], reticulocytes [72], and cutaneous and pulmonary fibroblasts [73]. Flow cytometric assays are also in development for biodosimetry [71] as are techniques for measuring DNA repair complexes such as histone H2AX [17-19].…”
Section: Physiological Processesmentioning
confidence: 99%